Nomenclatural validation of three names of Cotoneaster (Rosaceae) from Central Asia - Grevtsova, Ganna; Turdiboev, Obidjon; Turdiboev, Shohbozbek; Esemuratova, Rabiga; Alieva, Namuna (Phytotaxa, 2026)
During the revision of herbarium materials preserved in the KW herbarium and analysis of original literature, the names Cotoneaster kirgizicus, C. russanovii, and C. tkatschenkoi were found to be invalidly published. In the present paper, these names are validated by designation of the holotypes and by reference to the descriptions and diagnoses provided in Grevtsova (1999), in accordance with the International Code of Nomenclature for algae, fungi, and plants (ICN). This study contributes to the clarification of the nomenclature and taxonomy of Cotoneaster in Central Asia.